Origin and methods of hypnotism - Kellogg, Royal S. (My University, 1896)
Introduction: “The quality of animal bodies rendering them susceptible to the influences of heaven and earth”—such were the extravagant and meaningless terms in which, one hundred and thirty years ago, Anton Mesmer defined his theory of animal magnetism. Odic force, somnambulism, electro-biology, mesmerism, hypnotism—these are some of the names that have been applied to the phenomena of hypnotism in their development from the supernatural to the scientific form. During the early period of his career, Mesmer cured—or pretended to cure—diseases by the application of magnets to various parts of the body. Later, however, the magnet was discarded and the magical healing fluid was transmitted to the patient by means of “magnetic passes” or hand applications. Mesmer’s fame spread rapidly after his arrival in Paris in 1778, and to accommodate the large number of applicants, the baquet was invented.
Citation: Kellogg, Royal S. Origin and methods of hypnotism. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Anton Mesmer; Hypnosis; Hypnotizing; History; Theses; Manuscripts (documents)